2020
DOI: 10.1002/bmc.4988
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile of curcumin self‐emulsifying drug delivery system in rats determined by ultra‐high performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry

Abstract: Curcumin (Cur) is a natural anticancer pigment, but its poor absorption and extensive metabolism limit its clinical applications. In this study, an ultra‐high performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry method was employed to investigate the metabolic profiles of a Cur self‐emulsifying drug delivery system (C‐SEDDS) in rat plasma, urine, bile and feces after oral administration at 100 mg/kg. Protein precipitation, solid‐phase and ultrasonic extractions were used to prepare dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The incorporation of bioactives such as vitamin E and curcumin in SEDDS showed improved oral bioavailability due to their enhanced solubilization and cellular uptake [ 125 , 126 ]. Recently, Xu, et al [ 127 ] identified the variation of the curcumin metabolites of curcumin in rats after administering three different curcumin formulations, namely, SEDDS, suspension, and a commercial phospholipid complex. The authors identified 34 curcumin metabolites using ultra-high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry technique (UPLC–MS).…”
Section: Self-emulsifying Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of bioactives such as vitamin E and curcumin in SEDDS showed improved oral bioavailability due to their enhanced solubilization and cellular uptake [ 125 , 126 ]. Recently, Xu, et al [ 127 ] identified the variation of the curcumin metabolites of curcumin in rats after administering three different curcumin formulations, namely, SEDDS, suspension, and a commercial phospholipid complex. The authors identified 34 curcumin metabolites using ultra-high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry technique (UPLC–MS).…”
Section: Self-emulsifying Drug Delivery Systemsmentioning
confidence: 99%
“…Thus, a portion of curcumin was conjugated to glucuronide in the intestine and then reaches the portal vein and liver to form glucuronide/sulfate conjugates [ 129 ]. Although Xu, Tang, Zhang, Yang and Yuan [ 127 ] found an increase in bioavailability for rats administered with SEDDS formulation, the quantification of such curcumin metabolites for the different formulations is required to underpin the pharmacokinetic pathway of the SEDDS formulations.…”
Section: Self-emulsifying Drug Delivery Systemsmentioning
confidence: 99%